Computational Hemodynamic Study of Healthy and Pathological Abdominal Aorta - Kandpal, Abhishek (My University, 2018)
It had been observed from last two decades that the morbidity and mortality rate due to cardiovascular disease increases in the significant manner. Mostly patients around the world are affected by heart disease and systemic disorder such as hypertension & arterial dilation typically called aneurysm. Only in India the mortality rate due to Cardiovascular Disease (CVD) increases up to 28 % until 2017. It has been widely observed that atherosclerosis is the primary cause of cardiovascular disease. In present work abdominal aneurysm (AA) is selected for computational investigation. The abdominal aneurysm is defined as the dilation of the abdominal aorta in lateral direction along the diameter. In this work computational investigation of hemodynamic study of aortic abdominal aorta in healthy and pathological (aneurysed) conditions are done. In computational study, the critical hemodynamics parameters such as wall shear stress about the circumferential location and axial flow velocity are considered. These parameters are taken at the mid plane perpendicular to flow direction of affected region. The another parameter which is flow recirculation is also analyzed for its effect on diseased condition. A comparative study is performed between the healthy and aneurysed (saccular & fusiform) condition of different sizes. The computation is performed on a three dimensional model created by patient specific DICOM image. The different aneurysm sizes and shape are taken from the cited literature. The results found that the flow velocity of the aneurysed model is oscillating in nature. The average flow velocity varies between 50 cm/sec to 80 cm/s for aneurysed model which is lower than healthy case (80 cm/s). The oscillatory shear stress is least (-0.3 Pa in fusiform 5.5 cm & 6 cm) at 0 degree position and maximum (-7.3 Pa in 5.5 cm saccular aneurysm at circumferential position 270 degree) in between 180 and 270 degree. The final conclusion of this work suggested that the aneurysm of 5.5 cm and greater than 5.5 cm is very critical and immediate sugerical intervention is required for preventing it from rupture (hemoharrge).
Master of Engineering- Thermal
Keywords: Aortic abdominal aneurysm; Saccular and Fusiform; Patient specific DICOM